2000
DOI: 10.1103/physrevb.61.1433
|View full text |Cite
|
Sign up to set email alerts
|

BCS to Bose crossover in anisotropic superconductors

Abstract: In this work we use functional integral techniques to examine the nearest neighbour attractive Hubbard model on a quasi-2D lattice. It is a simple phenomenological model for the high-Tc cuprates that allows both extended (non-local) s-and d-wave singlet superconductivity as well as mixed symmetry states. The Hartree-Gor'kov mean field theory of the model has a finite temperature phase diagram which shows a transition from pure s-wave to pure d-wave superconductivity, via a mixed symmetry s + id state, as a fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…19 They found that for any coupling the s wave has the lowest critical temperature, except for a small region near half filling, where the Van Hove singularity of density of states weighted with the angular factors stabilizes the d-wave phase. The presence of the hard-core repulsion allows d-wave superconductivity to appear on a much larger portion of the phase diagram.…”
Section: Discussionmentioning
confidence: 99%
“…19 They found that for any coupling the s wave has the lowest critical temperature, except for a small region near half filling, where the Van Hove singularity of density of states weighted with the angular factors stabilizes the d-wave phase. The presence of the hard-core repulsion allows d-wave superconductivity to appear on a much larger portion of the phase diagram.…”
Section: Discussionmentioning
confidence: 99%
“…In this Section we consider the problem of d−wave pairing in 2D at zero temperature both in lattice [167][168][169][170][171] and in continuum models [172,173]. The motivation for considering this type of pairing is the experimental observation in the ARPES and other measurements [4,8,[13][14][15]] of a d x 2 −y 2 symmetry in HTSC.…”
Section: Crossover In the Models With D-wave Pairingmentioning
confidence: 99%
“…In what follows we consider a purely d-wave saddle point, and neglect completely a possible s-wave component. Being small at the Fermi surface near half filing, the amplitude of the s-wave order parameter is expected to be completely suppressed by the dominate d-wave component [39].…”
Section: Model and The Superconducting Saddle Pointmentioning
confidence: 99%